Cholestasis-Associated Pruritus and Its Pruritogens - Langedijk, Jacqueline A. G. M.; Beuers, Ulrich H.; Oude Elferink, Ronald P. J. (Frontiers in Medicine, 2021)
Pruritus is associated with multiple cholestatic disorders, including primary biliary cholangitis (PBC), primary sclerosing cholangitis (PSC) and inherited progressive familial intrahepatic cholestasis (PFIC). Chronic pruritus is, besides fatigue, the most debilitating symptom in these disorders. Consequently, patients suffer from sleep deprivation, loss of concentration, auto-mutilation and sometimes even suicidal ideations. Current therapy consists of four consecutive recommended treatments, which are often insufficient in effectively reducing cholestasis-associated pruritus. Therefore, also experimental therapeutic approaches are required to improve the patients’ quality of life. However, the molecular mechanisms of cholestasis-associated pruritus are still unclear and the involved pruritogens are indecisive. This article reviews the current state of research on pruritogens and their receptors, and shortly discusses the most recent experimental therapies.